2021
DOI: 10.1002/soej.12506
|View full text |Cite
|
Sign up to set email alerts
|

Profit‐enhancing entries in mixed oligopolies

Abstract: Mixed oligopolies are characterized by private and public enterprises. Previously, entry into these markets was restrictive. It has since been relaxed by deregulations, and as a result, private firms have entered mixed oligop-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The results of this study can further be examined in more general settings. Future studies may consider a convex cost function as in Matsumura and Okamura (2015) for the interdependent payoffs between public and private firms to find the optimal privatization policy, or as Haraguchi and Matsumura (2021), who explored how the number of private firms affects the profit of each private firm in mixed oligopolies. Perhaps, different settings could change the probability of domestic welfare reduction of tariff simplification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study can further be examined in more general settings. Future studies may consider a convex cost function as in Matsumura and Okamura (2015) for the interdependent payoffs between public and private firms to find the optimal privatization policy, or as Haraguchi and Matsumura (2021), who explored how the number of private firms affects the profit of each private firm in mixed oligopolies. Perhaps, different settings could change the probability of domestic welfare reduction of tariff simplification.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that the optimal subsidy yields the efficient production allocation if privatization is not implemented; however, once the public firm is privatized, it overproduces under the optimal subsidy. Haraguchi and Matsumura (2021) examined how the number of private firms affects the profit of each private firm in mixed oligopolies. Using a linear‐quadratic production cost function, Haraguchi and Matsumura (2021) revealed that if the degree of privatization is exogenous, the profit of each private firm reduces with the number of private firms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these entry restrictions have been lowered significantly in the past few decades. Consequently, entry deregulation policies in mixed oligopoly markets have become popular subjects in the literature (e.g., Matsumura and Kanda, 2005;Brandão and Castro, 2007;Haraguchi and Matsumura, 2021). Matsumura and Kanda (2005) demonstrate how complete nationalization is always the optimal policy in the long run when the private firms with free entry are owned by domestic investors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our experiments with this make clear that the extent of inefficiency becomes a new critical variable, but it is also clear that the role to relative sales will likely remain 7 . A generalization would be to relax the current assumption that k=1 in the quadratic cost function C=kqi2 (see Haraguchi & Matsumura, 2021, for an example in which this generalization matters). This makes k a critical determinant and an interior solution requires bounds on k.…”
Section: Robustness and Extensionsmentioning
confidence: 99%